2013
DOI: 10.1097/rct.0b013e31829d44fa
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Experience With Solid Pseudopapillary Neoplasms

Abstract: Objective Solid pseudopapillary neoplasms (SPNs) are low-grade malignancies with an excellent prognosis, albeit with the potential for metastatic disease. This study details our institution's experience with the diagnosis and treatment of SPN, including clinical presentation, multimodality imaging findings, and potential predictors of aggressive tumor behavior. Materials and Methods The institutional pathology database was searched through for all cases of SPN since 1988, yielding 51 patients. The electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 25 publications
1
9
0
1
Order By: Relevance
“…Owing to the covert manifestations, pancreatic SPTs are usually picked up by imaging examinations 28 . Typical imaging characteristics of pancreatic SPTs are described as encapsulated masses with solid and cystic components and frequent internal hemorrhage 29 . Although SPTs have typical radiological features, some of them were still preoperatively misdiagnosed for pancreatic cystic neoplasms 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the covert manifestations, pancreatic SPTs are usually picked up by imaging examinations 28 . Typical imaging characteristics of pancreatic SPTs are described as encapsulated masses with solid and cystic components and frequent internal hemorrhage 29 . Although SPTs have typical radiological features, some of them were still preoperatively misdiagnosed for pancreatic cystic neoplasms 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al[ 31 ] and Xu et al[ 35 ] showed that positive status for Ki-67 correlated with malignancy of SPTP, while Yang et al[ 8 ] did not demonstrate any association between the Ki-67 index and malignant SPTP. Most other studies[ 20 , 23 , 26 , 27 , 57 , 58 ] found no significant differences between benign and malignant SPTP, including age, sex, symptomatology, laboratory data, tumor marker, tumor size and location, tumor composition, growth pattern, and histopathology. Thus, malignancy cannot be easily predicted on the basis of preoperative findings and immunohistochemical patterns.…”
Section: Predictors Of Malignancymentioning
confidence: 94%
“…Due to the arbitrary criteria of malignancy used, and rarity of the disease with small proportion of malignancy, conflicting results have been reported about factors associated with malignant potential across institutions[ 8 , 20 , 23 , 24 , 26 , 27 , 30 , 31 , 35 , 36 , 38 , 39 , 56 - 58 ] (Figure 4 ). Butte et al[ 24 ] found that patients with malignant SPTP presented with larger tumor size ( P < 0.005).…”
Section: Predictors Of Malignancymentioning
confidence: 99%
“…Despite the large size of these tumors, vascular encasement or occlusion is quite rare (13%), although the large size of the masses sometimes leads to considerable displacement of the adjacent vasculature. MRI is superior to CT in distinguishing certain tissue characteristics, such as hemorrhage, cystic degeneration, or the presence of a capsule, and may enable correct diagnosis [ 16 ]. CT scans might help to diagnose SPNs accurately in 80% of the cases [ 17 ].…”
Section: Discussionmentioning
confidence: 99%